Pemilihan vendor trucking pengiriman produk kimia menggunakan metode ahp dan topsis di pt. Chandra asri pacific - Yusril, Lenggana Jauhar; Syafrianita; Nurlaela Kumala, Dewi (Jurnal Manajemen Rekayasa dan Inovasi Bisnis, 2025)
Trucking vendor selection is a crucial aspect in supporting smooth distribution and sustainability and company reputation. This study aims to determine the final weight of the selected criteria and sub-criteria as well as the final weight of vendor alternatives and to rank vendor alternatives based on previously weighted criteria. The company does not yet have fixed criteria in vendor selection so that the company has difficulty in choosing a vendor. This study uses the AHP and TOPSIS methods. From this study, the results of Responsive with a weight of 0.339 with sub-criteria of accuracy in handling complaints, speed in handling complaints and ease of communication, Reliability with a weight of 0.319 with sub-criteria of fleet availability, number of fleets, and ability to handle dangerous goods, Service with a weight of 0.256 with sub-criteria of timeliness, provision of insurance, and guarantee of results, Price with a weight of 0.086 with sub-criteria of price level, payment negotiation, and price stability. Based on the weight value of the AHP calculation, then look for the preference value and ranking of alternative vendors, with the results of PT. Jatim Petroleum Transport with a percentage value of 59.91%, PT. Agung Makmur Jaya percentage value 20.10%, PT Cakra Indo percentage value 19.99%. Alternative ranking of shipping vendors found that vendor PT. Jatim Petroleum Transport is ranked first and in second place PT. Agung Makmur Jaya, while in the last rank is PT. Cakra Indo.